A comparison of students’ performance in an online introductory managerial accounting course with hybrid classroom setting - Aly, Ibrahim M. (Canadian Journal of Higher Education, 2013)
This study compared the academic achievement between undergraduate students taking an introductory managerial accounting course online (N = 104) and students who took the same course in a hybrid classroom setting (N = 203). Student achievement was measured using scores from twelve weekly online assignments, two major online assignments, a final examination held on campus, and overall course performance. This study found that students receiving only online instruction were as successful as students receiving hybrid classroom instruction. These findings suggest that course instruction and pedagogy are more important for student learning than the type of media delivery, and online instructors should focus their effort on quality in developing online courses.